2005
DOI: 10.1038/sj.jea.7500418
|View full text |Cite
|
Sign up to set email alerts
|

Child dermal sediment loads following play in a tide flat

Abstract: Dermal contact with sediment is sometimes identified as a pathway of concern in risk assessments. Dermal exposure to sediment is poorly characterized and exposure assessors may rely on default soil adherence values. The purpose of this study was to obtain sediment adherence data for a genuine exposure scenario, child play in a tide flat. This study reports direct measurements of sediment loadings on five body parts (face, forearms, hands, lower legs and feet) after play in a tide flat. Each of nine subjects pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…Data on soil intake (assumed similar for sediment), sediment adherence and absorption factors were taken from the literature: the US EPA's Exposure Factors Handbook, Child-Specific Exposure Factors Handbook, Risk Assessment Guidance for the Superfund, and a Swedish draft guideline on contaminated soil [16][17][18][19][20][21]. However, the uncertainty is substantial and the reviewed literature seems to suggest that the absorption factors for PAH are overestimated [22][23][24][25][26].…”
Section: Exposure Factor Datamentioning
confidence: 99%
“…Data on soil intake (assumed similar for sediment), sediment adherence and absorption factors were taken from the literature: the US EPA's Exposure Factors Handbook, Child-Specific Exposure Factors Handbook, Risk Assessment Guidance for the Superfund, and a Swedish draft guideline on contaminated soil [16][17][18][19][20][21]. However, the uncertainty is substantial and the reviewed literature seems to suggest that the absorption factors for PAH are overestimated [22][23][24][25][26].…”
Section: Exposure Factor Datamentioning
confidence: 99%
“…These estimates were based on professional judgment and were considered by TCEQ (2007) to be upper end estimates based on high frequency use. In the small study of sediment adherence factors for children playing at tidal flats immediately adjacent to a Rhode Island town, Shoaf et al (2005a) informally surveyed parents on their children's time spent at the area and provided a median estimate of 12 h per week playing in sediments during the warmer months of the year. In the case of teens and adults, Richardson and Stantec (2013) reported that on a typical day less than 2% of Canadians engage in "other outdoor activities" based on a Statistics Canada dataset collected in 2010 as part of the General Social Survey, Cycle 24 (Statistics Canada 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although the values provided in Shoaf et al (2005b) were developed using adults (as compared to Shoaf et al [2005a] developed for children playing in a tidal flat), there is no obvious reason as to why the Shoaf et al (2005b) adherence factors measured in adults could not also occur with children. In addition, the sediments were finer in the adult study which could also contribute to the higher adherence factors.…”
Section: Sediment Loading Onto Hands (Sl Hands )mentioning
confidence: 98%
See 2 more Smart Citations